Variation in flavonoids in a collection of peppers (Capsicum sp.) under organic and conventional cultivation: effect of the genotype, ripening stage, and growing system. (21st January 2020) - Ribes‐Moya, Ana M; Adalid, Ana M; Raigón, Maria D; Hellín, Pilar; Fita, Ana; Rodríguez‐Burruezo, Adrián
Abstract: BACKGROUND: In recent years, the acreage used for organic agriculture and the demand for organic fruit and vegetables have increased considerably. Given this scenario, landraces, such as Capsicum landraces, can provide valuable germplasm. Capsicum peppers are very interesting because of their high phenolic content, and particularly their flavonoid content, which provides a high added value. Moreover, the broad genetic diversity in local varieties expands the opportunities for adaptation to organic production and for exploiting genotype × environment interactions to select peppers with the highest phenolic content. RESULTS: In this work, the main flavonoids of peppers were exhaustively evaluated over 2 years in a wide collection of heirlooms, both unripe and fully ripe, under organic and conventional cultivation. The genotype and ripening stage contributed to a high degree to the variation in flavonoids. The growing system influenced this variation to a lesser extent. Luteolin and quercetin showed the highest contributions to total phenolic content (70% and > 20%, respectively) at both ripening stages, while myricetin, apigenin, and kaempferol showed lower contributrions. The average flavonoid content was higher in ripe fruits, and organic management significantly increased the accumulation of total flavonoids and luteolin. Positive correlations between flavonoids were found at both ripening stages, especially between main flavonoids luteolin and quercetin and between kaempferol and quercetin ( ρ > 0.7). CONCLUSION: Genotype × environment interaction enabled the identification of accessions with high flavonoid content grown under organic conditions at both ripening stages, particularly total flavonoids and luteolin at the fully ripe stage. Our results reinforce the importance of a wide genetic variation and of considering different ripening stages and growing conditions for breeding high‐quality peppers. © 2020 Society of Chemical Industry